Model Kebijakan Pengembangan Energi Baru dan Terbarukan di Provinsi Banten - Ramdani, Deni Fauzi; Febriasari, Arifina (Universitas Medan Area, 2018)
This research is motivated by the existence of the potential of New and Renewable Energy (EBT) in Banten Province. The purpose of this study is to analyze how to policy development model Â and potential policies for Renewable Energy (EBT) in Banten Province. The research method used is a qualitative descriptive approach with primary data collection techniques through interviews and observations as well as secondary data in the form of searching various sources and literature both from government documents and reporting on print and electronic mass media. The results of this study are the analysis of innovation and development of Banten Province EBT potential policies, namely the identification of Priority Policies for New and Renewable Energy Policy, innovation and development of EBT policies which include the initial conditions of developing Banten Province EBT potential which includes resources, politics and regulation, culture the community and the bureaucracy / institution as the base capital for the development of the EBT policy in Banten Province and an analysis of the modification of the Banten Province EBT potential policy system model.Â